Tailoring the Adsorption-Induced Flexibility of a Pillared Layer Metal-Organic Framework DUT-8(Ni) by Cobalt Substitution - Ehrling, Sebastian; Mendt, Matthias; Senkovska, Irena; Evans, Jack D.; Bon, Volodymyr; Petkov, Petko; Ehrling, Christoph; Walenszus, Francesco; Poeppl, Andreas; Kaskel, Stefan (Chemistry of Materials, 2020)
Controlling the adsorption behavior of switchable porous materials is essential to pave the way for their successful implementation in highly selective separation and sensing applications. The switchable MOF M2(2,6-ndc)2(dabco) (DUT-8(M), where DUT = Dresden University of Technology, 2,6-ndc = naphthalene dicarboxylate, dabco = 1,4-diazabicyclo-[2.2.2]-octane, and M = Ni and Co) shows distinct differences in gating adsorption behavior depending on the transition metal of the node. Both DUT-8(Ni) and DUT-8(Co) transform into the closed pore phase after solvent removal. The nickel-containing compound shows high responsivity and gate opening in response to nitrogen adsorption, p/p0 = 0.1 (77 K), resulting in a huge pore volume change, while the Co compound remains in a closed pore phase and is completely nonresponsive to nitrogen at 77 K. Herein, we demonstrate the gradual tuning of the gate opening pressure in DUT-8(M), upon nitrogen adsorption, by partially substituting nickel with cobalt in a series of mixed metal MOFs. The substitution mechanism was analyzed by powder X-ray diffraction (PXRD), solid-state UV/vis spectroscopy, inductively coupled plasma-optical emission spectroscopy elemental analysis, and energy-dispersive X-ray spectroscopy. In particular, continuous wave electron paramagnetic resonance (EPR) spectroscopy demonstrated the coexistence of Ni/Ni, Co/Ni, and Co/Co paddle wheel (PW) units. The gradual substitution of Ni in DUT-8(Ni) with Co allows continuous tuning of the gate opening pressure from p/p0 0.1 to 0.75 (75% Co). The integration of Ni/Co-PWs into this pillared layer MOF has enabled, for the first time, in situ monitoring of this gating phenomenon via parallelized adsorption of N2 (71 K) and EPR spectroscopy. These observations can be compared directly with in situ PXRD data collected during N2 adsorption at 77 K. These complementary techniques reveal unique mechanistic insights into the structural changes of the PWs during the gating process. In addition, the experimental observations are supported by computational methods using density functional theory.
CRIS-Team Scopus Importer:2022-04-14